Prenatal Alcohol Exposure as a Case of Involuntary Early Onset of Alcohol Use: Consequences and Proposed Mechanisms From Animal Studies - Gaztañaga, Mirari; Angulo-Alcalde, Asier; Chotro, M. Gabriela (Frontiers in Behavioral Neuroscience, 2020)
Prenatal alcohol exposure has been found to be an important factor determining later consumption of this drug. In humans, despite the considerable diversity of variables that might influence alcohol consumption, longitudinal studies show that maternal alcohol intake during gestation is one of the best predictors of later alcohol use from adolescence to young adulthood. Experimental studies with animals also provide abundant evidence of the effects of prenatal alcohol exposure on later alcohol intake. In addition to increased consumption, other effects include enhanced palatability and attractiveness of alcohol flavor as well as sensitization to its sensory and reinforcing effects. Most of these outcomes have been obtained after exposing rats to binge-like administrations of moderate alcohol doses during the last gestational period when the fetus is already capable of detecting flavors in the amniotic fluid and learning associations with aversive or appetitive consequences. On this basis, it has been proposed that one of the mechanisms underlying the increased acceptance of alcohol after its prenatal exposure is the acquisition (by the fetus) of appetitive learning via an association between the sensory properties of alcohol and its reinforcing pharmacological effects. It also appears that this prenatal appetitive learning is mediated by the activation of the opioid system, with fetal brain acetaldehyde playing an important role, possibly as the main chemical responsible for its activation. Here, we review and analyze together the results of all animal studies testing these hypotheses through experimental manipulation of the behavioral and neurochemical elements of the assumed prenatal association. Understanding the mechanisms by which prenatal alcohol exposure favors the early initiation of alcohol consumption, along with its role in the causal pathway to alcohol disorders, may allow us to find strategies to mitigate the behavioral effects of this early experience with the drug. We propose that prenatal alcohol exposure is regarded as a case of involuntary early onset of alcohol use when designing prevention policies. This is particularly important, given the notion that the sooner alcohol intake begins, the greater the possibility of a continued history of alcohol consumption that may lead to the development of alcohol use disorders.